Equine non-healing corneal ulcers: a retrospective evaluation of 57 cases (2001–2017) - Prucha, Vera J. S.; Tichy, Alexander; Nell, Barbara (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2020)
Background and objectives Non-healing corneal ulcers (NHCU) are a common problem in equine practice and several treatment options are available with different success and healing times. The aim of this retrospective study was to evaluate and to compare treatment protocols, clinical courses, corneal healing time and outcomes of NHCU.Methods From December 2001 to December 2017, a total of 57 horses with NHCU were presented at the Vetmeduni Vienna. Recorded data included affected eye, signalment, clinical symptoms, season of diagnosis, treatment protocols, complications and corneal healing rate.Results Sixty-three eyes were diagnosed with a NHCU. Follow-up information was available for 48/63 eyes. For those treated medically mean corneal healing time was 15.7 days (± SD 12.0). Medical treatment included topical antibiotics, antimycotics, cycloplegics, and systemic anti-inflammatory drugs. Twelve eyes received treatment with a poly-carboxymethylglucose-sulfate regenerating agent (Cacicol®; Thea Pharma GmbH, Wien, Austria). Other common additional treatments included debridement with an iodine drenched cotton tip (48 eyes; 76.2 %) and diamond burr debridement (30 eyes; 47.6 %). A bandage contact lens (BCL) was used for 10 eyes. Each eye received at least one additional treatment, although none of them led to a statistically significant alteration in healing time. Only usage of a BCL significantly increased healing time when compared to not using a BCL (p = 0.035). When all treatments failed, superficial keratectomy with placement of a conjunctival flap was performed. Secondary complications included stromal cellular infiltration, keratomycosis, keratomalacia, and corneal abscess formation.Conclusions Results correlated with those previously described and thus demonstrated the difficulty and complexity of this disease. Further research is needed to determine an optimal treatment protocol for non-healing ulcers in horses.Clinical relevance Since NHCUs are a commonly encountered problem in equine practice a reliable treatment protocol is required. This study reflects the problems with those ulcers and provides several protocols for possible treatments.
Keywords: Eye disease; non-healing ulcer; regenerating agent; debridement; horse; cornea